Infinite Boundary Value Problems for Second-Order Nonlinear Impulsive Differential Equations with Supremum - Piao-Piao Shi; Wen-Xia Wang (Discrete Dynamics in Nature and Society)
We investigate the infinite boundary value problems for second-order impulsive differential equations with supremum by establishing a new comparison result and using the lower and upper solution method, and obtain the existence results for their maximal and minimal solutions.